Conceptualizing the moderating role of CEO power and ownership concentration in the relationship between audit committee and firm performance: empirical evidence from Pakistan - Javeed, Sohail Ahmad; Ong, Tze San; Latief, Rashid; Muhamad, Haslinah; Soh, Wei Ni (Multidisciplinary Digital Publishing Institute, 2021)
Firms in developing economies generally find ways to enhance their reputation and growth in the international market. In this context, an Audit Committee (AC) is composed of multiple skilled members that control and monitor auditing activities and present a transparent image of their firm, which automatically attracts investors and builds investor confidence. Therefore, this study used CEO power and ownership concentration as moderating factors to examine the connection between AC and firm performance. For this purpose, this study used the data of Pakistani manufacturing firms for the period 2008 to 2018 and applied the Ordinary Least Square (OLS) method, the Fixed Effect (FE) model, and the Generalized Method of Moments (GMM). To check the robustness of the results, this study used a Feasible Generalized Least Square (FGLS) model. The findings of this study contended that AC and firm performance have a positive association with each other. Moreover, the findings revealed that CEO power positively influenced firm performance. Furthermore, lower ownership concentration is a valuable approach to maximize a firm’s performance. Importantly, the outcomes concluded that AC and firm performance have a positive connection with the moderating effects of CEO power. Moreover, AC and firm performance also have a positive association with the moderating effect of ownership concentration.